The Effect of Competence, Workload and Compensation on the Performance of Family Assistance Team (FAT) Cadres in Reducing the Risk of Stunting in the Buleleng District Area - I Putu Aprilia Pratama; Henry Sudiyanto; Eka Diah Kartiningrum; Sulis Diana (Universitas STRADA Indonesia, 2025)
Background: Stunting as a health problem is influenced by various factors including inappropriate nutrition and feeding practices. Family Assistance Team (FAT) cadres have an important role in providing assistance, but challenges in the field related to competence and high workload are a barrier to achieving optimal performance. Purpose: This study aims to analyze the influence of competence, workload, and compensation on the performance FAT cadres in reducing the risk of stunting in Buleleng District. Methods: This study uses an analytical observational design with a cross-sectional approach. The population of this study includes all FAT cadres who are actively serving in Buleleng District, Buleleng Regency, totaling 288 people. The research sample was taken using the proportional stratified random sampling technique. The samples was calculated using the Slovin formula resulting 168 cadres as respondents. Results: The results showed that the majority of FAT cadres' competence was good (93.5%), most of the workload was high (64.3%) but only 25% stated that the compensation received was good. The results of data analysis were carried out using multiple linear regression. The results showed that the majority of competencies had a positive (p-value 0.000 < 0.005) and significant effect on cadre performance, while workload (p-value 0.522 > 0.005) and compensation (p-value 0.828 > 0.005) showed no significant effect. Conclusion: Increased competence and compensation, as well as good workload management, are very important to support the performance of FAT cadres in stunting prevention. Therefore, it is important for FAT cadres to attend many trainings and workshops that are in accordance with their needs in order to improve competence. Thus, they will have good performance in reducing stunting.